SARS-CoV-2 evolution among patients with immunosuppression in a nosocomial cluster of a Japanese medical center during the Delta (AY.29 sublineage) surge - Hosaka, Yoshie; Yan, Yan; Naito, Toshio; Oyama, Rieko; Tsuchiya, Koji; Yamamoto, Norio; Nojiri, Shuko; Hori, Satoshi; Takahashi, Kazuhisa; Tabe, Yoko (Frontiers in Microbiology, 2023)
Background: Previous studies have shown that patients with immunosuppression tend to have longer-lasting SARS-CoV-2 infections and a number of mutations were observed during the infection period. However, these studies were, in general, conducted longitudinally. Mutation evolution among groups of patients with immunosuppression have not been well studied, especially among Asian populations. Methods: Our study targeted a nosocomial cluster of SARS-CoV-2 infection in a Japanese medical center, involving ward nurses and inpatients. Whole-genome sequencing analyses were performed to examine mutation changes. In addition, sequences of samples prior to this cluster, as well as from the Tokyo metropolitan area during the timeframe of the cluster, were used to assess the phylogenetical distinction of this cluster. Results: 6 nurses and 14 inpatients were identified as a nosocomial cluster from September 14 through 28, 2021. 92.9% of infected patients (13 out of 14) were either cancer patients and/or receiving immunosuppressive or steroid treatments. Compared to wild type SARS-CoV-2, a total of 46 mutations were found in the 20 cases: 1 index group and 9 sub-groups, with additional one to three mutations. In COVID-19 symptomatic cases, the frequency of mutation acquisition was significantly higher in cancer patients (5/5 cases) when compared to nurses (1/4 cases; 3 within the index type; 1 post cancer surgery with additional mutations) (Fisher's exact test P <0.048). Conclusion: Our study of a nosocomial SARS-CoV-2 cluster highlights mutation acquisition during transmission. More importantly, it provided new evidence emphasizing the need to further improve infection control measures to prevent nosocomial infection among immunosuppressed patients.